Subsunción adjetival en sentencias penales del Tribunal Supremo español - Montiel Domínguez, José Luis; Sánchez Gómez, Coronada; Cristea, Mihaela Delia (Del Español. Revista de Lengua, 2023)
This paper belongs to the recent studies about the modernization of legal Spanish, because we adopt a semantic approach to the analysis of two types of adjectives (gradable and nongradable) in the argumentation of the penal sentences by the Supreme Court of Spain. The text criticizes the subjective assessment inside the sentences, which can we infer from the employment of gradable adjectives as a reply to the pleas or allegations by lawyers or prosecuting attorneys. On the contrary, we defend a legal argumentation based upon the more objective adjectivization stem from the penal types. Besides, we offer a method of subsumption or reduction of the legal argumentation based upon a causal formula which enables the use of an adjective of these categories.